PERSEPSI PEROKOK DAN PELAKU USAHA ROKOK ELEKTRIK TERHADAP KEBIJAKAN PENERAPAN CUKAI ROKOK ELEKTRIK SERTA PENGARUHNYA TERHADAP POLA KONSUMSI - Sabilla, Cut Nur; Januraga, Pande Putu (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT Tobacco represents a significant economic commodity, albeit with deleterious health implications. Prior to the resolution of this issue, electronic cigarettes have been introduced in Indonesia under the assertion of being a healthier alternative or a cessation aid for conventional smoking. The imposition of the first electronic cigarette tax took effect in 2018 through Minister of Finance Regulation No. 146/PMK.010/2017, levying a tax rate of 57%. This study adopts an exploratory qualitative approach employing purposive sampling, with in-depth interviews as the chosen methodology to assess the tax's impact on consumption and sales trends. The findings indicate that smokers did not curtail their consumption post-tax implementation, and there was no observable reduction in electronic cigarette sales. Evidently, the government-imposed tax has not thus far succeeded in attenuating the prevalence of electronic cigarette consumption within the population. Key word : E-Cigarettes, Excise tax, Consumption